2014
DOI: 10.18632/oncotarget.2291
|View full text |Cite
|
Sign up to set email alerts
|

A central role for TRPS1 in the control of cell cycle and cancer development

Abstract: The eukaryotic cell cycle is controlled by a complex regulatory network, which is still poorly understood. Here we demonstrate that TRPS1, an atypical GATA factor, modulates cell proliferation and controls cell cycle progression. Silencing TRPS1 had a differential effect on the expression of nine key cell cycle-related genes. Eight of these genes are known to be involved in the regulation of the G2 phase and the G2/M transition of the cell cycle. Using cell synchronization studies, we confirmed that TRPS1 play… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
48
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 79 publications
4
48
0
Order By: Relevance
“…In sporadic breast cancer, an upregulated TRPS1 expression was previously reported which is in line with our findings in the sporadic subset of control cases . In sporadic breast cancer TRPS1 is linked to the stimulation of cell proliferation and angiogenesis and the promotion of cell cycle progression . Furthermore, TRPS1 overexpression was proposed as a prognostic marker in early stage breast cancer due to an association with improved overall survival and disease‐free survival in these tumors .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In sporadic breast cancer, an upregulated TRPS1 expression was previously reported which is in line with our findings in the sporadic subset of control cases . In sporadic breast cancer TRPS1 is linked to the stimulation of cell proliferation and angiogenesis and the promotion of cell cycle progression . Furthermore, TRPS1 overexpression was proposed as a prognostic marker in early stage breast cancer due to an association with improved overall survival and disease‐free survival in these tumors .…”
Section: Discussionsupporting
confidence: 91%
“…Either mutation or deletion of this gene causes a disease called trichorhinophalangeal syndrome. Previous studies have shown that TRPS1 is expressed in several human malignant tumors and implied an important function in tumor growth, cell cycle, angiogenesis, apoptosis, cell proliferation, migration and metastasis …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, its role in cancer progression remains largely unknown. Study by Wu et al proposed that TRPS1 acted as a central hub in the control of cell cycle and proliferation during cancer development [35]. Our study found that TRPS1 was significantly high expressed both in BC samples and BC cell lines, and co-expressed with the expression of ERBB2, supporting the critical role of TRPS1 in BC initiation or progression.…”
Section: Discussionsupporting
confidence: 78%
“…One of these intergenic palindromes is absent in many tumor samples whereas there are no changes observed in normal samples; other intergenic palindromes got smaller in tumors with no changes in normal samples. TRPS1 gene belongs to the family of transcription factors and may have role in regulating cell proliferation and growth [25]. This gene is localized in chr8q23-24.1, and this region is known to be highly amplified in breast and prostate cancers.…”
Section: Discussionmentioning
confidence: 99%